Role of Active Site and CO2‐Interacting Surface Species in Dry Reforming of Methane over Strontium Promoted Ni Catalyst Supported by Lanthanum‐Zirconia - Kenit Acharya; Ahmed S. Al‐Fatesh; Anis H. Fakeeha; Ahmed E. Abasaeed; Othman Alothman; Hammad Ahmad Jan; Naif Alarifi; Jehad K. Abu‐Dahrieh; Dr. Rawesh Kumar (ChemistryOpen)
Abstract In the context of global warming, the dry reforming of methane (DRM) has gained significant attention due to its ability to simultaneously deplete two greenhouse gases, i. e. CH4 and CO2, and generate syngas. Herein, strontium‐promoted Lanthanum‐zirconia supported Ni catalysts are investigated for DRM and characterized by X‐ray diffraction, surface area and porosity, FTIR‐RAMAN spectroscopy, and temperature‐programmed experiments. The Ni/LaZr catalyst contains formate and oxycarbonate‐like CO2‐interacting species, while strontium‐promoted catalysts have additional ionic CO32− species. The current catalyst system of 2 % strontium‐promoted Ni/LaZr has active sites derived from three types of NiO: easily reducible, moderately interacted, and strongly interacted. During the DRM reaction over the current system, CO2 is a better oxidant than O2 for removing carbon deposits. Additionally, the catalysts attain higher reducibility under oxidizing gas (CO2) and reducing gas (H2) during the DRM reaction. For optimal hydrogen yield of approximately 60 % within 420 minutes of operation over Ni2Sr/LaZr catalyst, a balance between the population of active site Ni and CO2‐interacting surface species is necessary.